Effectiveness of self-hypnosis In Overcoming Sleep Disorders In Menopauseal Women - Marizi, Lelita; Emilia, Okta; Permatasari, Anggun; Wahyuni, Sari; Nurayuda, Nurayuda (Poltekkes Kemenkes Palembang, 2023)
Menopause is the natural end of the menstrual cycle, a woman is said to have reached menopause when she has not had menstruation again for at least 12 months. In Indonesia, data from the Central Bureau of Statistics shows that 15.2 million women out of 118 million women experience menopause, so with the high prevalence of menopausal women, symptoms that can make a woman's quality of life worse should be addressed with various efforts.Sleep disorders commonly experienced by menopausal women can reduce the quality of life f or women when they enter menopause. Methods This study used a quantitative research type using the Quasi Experiment method with two pretest- posttest control groups, this study analyzed the effectiveness of self - hypnosis in the experimental group whose samples were observed before and after being given treatment. Results Based on the results of the Wilcoxon statistical test, there is a significant effect of audio self - hypnosis on the level of sleep disturbance in menopausal women obtained a P-value of 0.0000 < 0.05. There is a significant effect of self - hypnosis on the level of sleep disturbances in menopause. Conclusion Based on the analysis of the discussion, it can be concluded that Self - hypnosis is effective for dealing with sleep disturbanc es during menopause.